Dataset supporting the proteomic differences found between excretion/secretion products from two isolates of Fasciola hepatica newly excysted juveniles (NEJ) derived from different snail hosts - Sánchez Di Maggio, Lucía (2019)
Here we present the proteomic profile datasets of two Fasciola hepatica NEJ isolates derived from different snail hosts: Lymnaea viatrix and Pseudosuccinea columella. The data used in the analysis are related to the article ‘A proteomic comparison of excretion/secretion products in Fasciola hepatica newly excysted juveniles (NEJ) derived from Lymnaea viatrix or Pseudosuccinea columella’ (Di Maggio et al., 2019)